The Validity of Applying State Space Model to Japanese Stock Market - Kurihara, Yutaka; Maeda, Shinichiro (International Journal of Economics and Financial Modelling, 2016)
This paper examines recent Japanese stock prices using the state space model. Time series analyses like the GARCH model have often been used for estimation or prediction, but state space analyses have not been used as often. Whether or not the validity of applying the state space model to the Japanese stock market is appropriate is examined in this study. Japan was in recession for over twenty years, and a large financial crisis hit all over the world including Japan in 2008. After that, Abenomics, a huge monetary expansion from 2013, has been conducted in Japan. This paper examines the two periods from 2008–2012 and from 2013–2017 and employs the state space model to examine the Japanese stock prices. The empirical results show that the state space model fits well to examine Japanese stock prices and components of trend is larger during the period of Abenomics. From the conduction of Abenomics, stock price has mainly been moving according to the movement of the trend.